ANALYSIS FINANCIAL PERFORMANCE OF RURAL BANKS IN INDONESIA - Mohammad Sofyan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
During the period 2006-2019 many rural banks were liquidated by Indonesia Deposit Insurance Corporation (LPS) which have an impact on the performance of rural banks. This study aims to determine the effect of CAR, LDR, OCOI and NPL on the ROA of Rural Banks in Indonesia. The results of the study show that CAR, LDR, and OER have a significant effect on ROA. Every increase in operating costs will result in a decrease in pre-tax profit which results in a decrease in ROA. NPL has no significant effect on ROA. because rural bank has a large CAR ratio to cover credit risk.